Characterization of Cholylglycine Hydrolase from a Bile-Adapted Strain of Xanthomonas maltophilia and Its Application for Quantitative Hydrolysis of Conjugated Bile Salts - Dean, Mariangela (American Society for Microbiology, 2002)
Purified bile salt hydrolase from bile-adapted Xanthomonas maltophilia displays Michaelis-Menten kinetics on cholylglycine and cholyltaurine and hydrolyzes bile salts also in crude bovine bile. The protein is a dimer and is resistant to proteinases and to heating at 55 to 60°C for up to 60 min, in agreement with calorimetric data.